SURGICAL MANAGEMENT OF MALE INCONTINENCE, WITH PROLENE MESH FIXING WITH PROLENE SUTURES; A PROSPECTIVE NOVEL STUDY FOR THE TREATMENT OF MALE INCONTINENCE AT TERTIARY CARE HOSPITAL - Abdullah, Aziz; Memon, Imran; Ahmed, Syed Farhan; Muhammad, Asim; Anwar, Adnan (Journal of Ayub Medical College Abbottabad, 2019)
Background: Urinary incontinence is an uncommon problem in males but has major impact on daily living. This study aimed to highlight the outcome of surgical treatment in terms of safety, efficacy and cost-effectiveness in the management of urinary incontinence. Methods: A Total of 48 patients, prospective experimental study, in the duration of 4 years conducted at Department of Urology, Liaquat National Hospital & Medical College. Patients having moderate to severe urinary incontinence for 1 year after transurethral resection of prostate, radical prostatectomy, road traffic accident with pelvic fracture causing neurologic damage were included in this study. Patients having mild incontinence, having multiple co-morbid conditions were excluded from this study. Outcome of surgery was noted during follow up visit after 13 month (median). The data was obtained and analysed by using SPSS version 20. Mean and standard deviation for quantitative data, frequency and percentage for categorical variables were presented. Results: Out of 48 patients having urinary incontinence, 28 (58.3%) had severe urinary incontinence while 20 (41.7%) had moderate incontinence. After surgery, 28 (58.3%) patient had no leakage all day, 12 (25%) had some leakage while bending and 8 (16.7%) had no improvement in symptoms. On ultrasound recorded after voiding in post-surgery patients, 40 (83.3%) had no residual found in bladder while 8(16.7%) could not be assessed due to persistence of urinary incontinence. Conclusion: Our study predicted that in patients having moderate to severe urinary incontinence, Prolene Mesh repair anchoring with Prolene suture can be an efficient and cost-effective treatment for the urinary incontinence with least complications. Keywords: urinary incontinence; Prolene Mesh repair surgery